THE INFLUENCE OF CONSUMER BEHAVIOR ON ONLINE PURCHASE DECISIONS THROUGH GOFOOD IN BANDUNG CITY - Joko Suhariyanto (Jurnal Ekonomi, 2023)
The objective of this research was to investigate the impact of consumer behavior on purchasing decisions made for food and beverages using the GoFood application as the medium for the investigation. One of the companies that runs as Indonesia's leading meal delivery service provider site is GoFood, which is owned and operated by GoFood. The business, which already faces competition from a number of other companies, is attempting to persuade consumers to continue using GoFood as a way to fulfill their requirements for placing food orders. This is particularly important in the city of Bandung, which is seeing a growing trend. Purposive sampling, which is a subtype of non-probability sampling, was utilized for this survey's collection of data using a Likert scale. The method for analyzing the data was multiple linear regression, and the results were interpreted with the help of the SPSS (Statistical Product Moment and Service Solution) program for windows version 20.0. According to the findings of the research, the consumer behavior (including cultural, social, personal, and psychological variables) on each modification as a whole was considered to be good criterion by the community.